Quantifying the movement patterns of international women's rugby sevens preparation training camp sessions - Griffin, J. A.; McLellan, C. P.; Presland, J.; Rathbone, E.; Keogh, J. W. L. (International Journal of Sports Science & Coaching, 2017)
Training camps in the present study consisted of four sessions over two to four days, to prepare players for international competitions. Training camps focused on improving the technical and decision making skills in context with team tactics, however it is unknown if the physical demands were being developed or maintained concurrently. Due to the unknown physical demands of training camps, the present study sought to quantify the movement patterns and compare sessions of preparation training camps for international women's rugby sevens players. Twenty-four international female sevens players (age 24 ± 5 years, height 168 ± 5 cm, body mass 68 ± 6 kg; mean ± SD) were monitored over seven training camps using Global Positioning System units with integrated triaxial accelerometers. Women's sevens players covered a median total distance of 3823m (relative distance of 44m/min) during training camp sessions that lasted for an average duration of 91 minutes. Sprints occurred 41 times and repeated sprints occurred 14 times during training sessions at a rate of 0.47 sprints per minute and 0.17 repeated sprints per minute. The present study indicated that as a result of the technical and tactical focus of training camps the physical demands maybe insufficient to enhance physiological adaptations. Instead it appears that players are being prepared for upcoming competition by reducing residual fatigue and optimising freshness. ABSTRACT FROM AUTHOR